Effectiveness of Yoga as a Complementary Therapy for Anorexia Nervosa: A Systematic Review - Massimiliano Buoli; Francesca Legnani; Monic Mastroianni; Letizia Maria Affaticati; Enrico Capuzzi; Massimo Clerici; Alice Caldiroli (International Journal of Yoga)
Anorexia nervosa (AN) is a severe psychiatric condition associated with high disability and mortality. The purpose of the present manuscript is to critically summarize evidence about the effectiveness of yoga for this condition. A bibliographic search was conducted in the main database sources (PubMed, Embase, and Scopus). Articles in English about the effectiveness of yoga in AN were included. Two hundred thirty-three articles were initially identified and 5 articles were included in the present review. With the exception of one study, all had several methodological limitations such as the presence of confounding factors (e.g., psychiatric comorbidity) or a too limited sample of patients. However, globally yoga seems to ameliorate AN symptoms, especially those regarding emotional dysregulation. Yoga is a candidate complementary treatment for the management of AN, but more randomized controlled studies with larger samples and limited bias are necessary to draw robust conclusions. It would be also interesting to verify in comparative trials the effectiveness of yoga with respect to other treatments such as psychotherapy or the administration of pharmacological compounds. Finally, the practice should be modified adapting to the specific needs of this type of patient.